Estimation of CPK, LDH, GOT and GPT Enzymes Activity in Serum of Abortion Women. - Farhan, Layla O (Al-Nahrain Journal of Science, 2018)
The current project was designed to study the biochemical aspects of serum of Abortion women for enzymes activities and to compare the recorded values with the standard values. The study group comprised of thirty abortion women and thirty normal women as control. Laboratory investigations including creatine phosphokinase (CPK), Lactate Dehydrogenase (LDH), glutamicoxaloacetic transaminase (GOT) and glutamic pyruvic transaminase (GPT) had been measured in abortion women and control. There were significant difference in CPK, LDH, GOT, and GPT, (P